Switching Scheme for Regenerative Braking Mode for BLDC Motor Driver - Teoh, Joe Yew; Yahya, Jabbar Al Fattah (Evolution in Electrical and Electronic Engineering, 2022)
At present, the BLDC motor is commonly used for an electrical vehicle due to its high efficiency, high frequency and able to regenerate energy. Research that uses MATLAB/Simulink and Arduino IDE software to construct the simulation and hardware to prove the BLDC motor with switching scheme is able to generate energy when the braking process is held on. The MATLAB/Simulink software is used for simulating the BLDC motor virtually. Before constructing the hardware needs to ensure the concept is true as well as able to get the expected result. The Arduino IDE software is used because the Arduino Uno will be used as a microcontroller in this project for controlling the switching scheme, braking system and speed sensor. The results show that the switching scheme is able to operate in regenerative braking mode. Therefore, it is important to study both simulation and hardware to ensure the study will be more accurate.